Optimization of Thawing Regimen for Cryopreserved Human Sperm at Normo- and Pathospermia - Pavlovych, Olena; Revenko, Olena; Gapon, Ganna (Problems of Cryobiology and Cryomedicine, 2016)
Due to the widespread development of assisted reproductive technologies an actual task is to improve current methods of sperm cryopreservation. We studied the morphological and functional states of the cryopreserved human sperm in normal and pathological conditions at different regimens of thawing. All samples were maintained above the mirror of liquid nitrogen with further heating of spermatozoa in a water bath (37, 50, 60,70°C) or maintaining at room temperature until the liquid phase appearance. Morpho- functional state of sperm was estimated by their motility and viability. Assessment of sperm chromatin was carried out using acridine orange staining. It was found that a thawing regimen of sperm at50°C (with pre-incubation of the samples in liquid nitrogen vapor at –150°C) after sperm cryopreservation by three-stage protocol effectively kept their motility without the changes of membrane integrity and nuclear chromatin state at normo- and asthenozoospermia. Thawing of sperm at room temperature under the same conditions was the most traumatic for human sperm both at normo- and asthenozoospermia. Probl Cryobiol Cryomed 2016; 26(1):45-52.